The eco‐hydrologic influence of the Three Gorges Reservoir on the abundance of larval fish of four carp species in the Yangtze River, China. Issue 1 (19th August 2016) - Ban, Xuan; Chen, Si; Pan, Bao‐Zhu; Du, Yun; Yin, Da‐Cong; Bai, Mu‐Chen
Abstract: The natural abundance of larval fish of four carp species has been affected adversely by the Three Gorges Reservoir in the Yangtze River. One of the methods to conserve fish is to regulate hydrology regimes to keep them optimal for species spawning. Thirty‐two hydrologic indicators (HIs) associated with the hydrologic regime of the spawning sites at the Jianli reach were analyzed with the range of variability approach. Outputs were correlated with abundance of larval fish by a genetic programming approach to explore the relationship between the hydrologic regime and fish abundance. Results showed that rate of rise for discharge and average monthly discharge in June, October, and December; rate of rise for water level, average monthly water level in May, June, July, October, and November, and 1‐, 3‐, 7‐, and 30‐day maximum water level; and high pulse duration for sediment concentration and average monthly sediment concentration in June, July, and October were key factors that affected fish species abundance. All of these HIs changed greatly after impoundment of the Three Gorges Reservoir since 2003. Discharge and water level played the dominant role in reproduction of four carp species when the change of sediment concentration kept stable. However, when the sediment concentration declined over the limited range, it replaced discharge and water level as having the dominant role in reproduction. Two relationships between abundance of larval fish and HIs were identified from genetic programming results to explore an indicator impact matrix for use in eco‐hydrologic management through change of some HIs to improve fish abundance.